2021
DOI: 10.1002/alr.22927
|View full text |Cite
|
Sign up to set email alerts
|

Innovative application of internal carotid artery embolization in salvage endoscopic nasopharyngectomy for recurrent nasopharyngeal carcinoma: A case‐matched comparison

Abstract: Background:The efficacy and safety of internal carotid artery (ICA) embolization as a treatment strategy in recurrent nasopharyngeal carcinoma (rNPC) patients with tumors invading the ICA remain unclear. Methods: We enrolled all rNPC patients with tumors invading the ICA, who underwent salvage endoscopic surgery. Using propensity scores to adjust for specific potential prognostic factors, a well-balanced cohort of 42 patients with limited rNPC was formed by matching each patient who underwent ICA embolization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In 2017, we found the risk of tumor invading the ICA, and applied the ICA embolization technique to rNPC patients with ICA invasion for the first time internationally, and improved the survival rate of such patients 14 . In 2022, we further reported that after pretreating the ICA with coil embolization before surgery, the 2‐year OS and PFS of these patients were as high as 90.5% and 71.3%, respectively, which were significantly higher than the rates of 53.3% and 33.0% in the nonembolization group, respectively 18 . Therefore, ICA embolization would further improve the survival rate of advanced rNPC in the Fudan rT staging.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In 2017, we found the risk of tumor invading the ICA, and applied the ICA embolization technique to rNPC patients with ICA invasion for the first time internationally, and improved the survival rate of such patients 14 . In 2022, we further reported that after pretreating the ICA with coil embolization before surgery, the 2‐year OS and PFS of these patients were as high as 90.5% and 71.3%, respectively, which were significantly higher than the rates of 53.3% and 33.0% in the nonembolization group, respectively 18 . Therefore, ICA embolization would further improve the survival rate of advanced rNPC in the Fudan rT staging.…”
Section: Discussionmentioning
confidence: 89%
“…14 In 2022, we further reported that after pretreating the ICA with coil embolization before surgery, the 2-year OS and PFS of these patients were as high as 90.5% and 71.3%, respectively, which were significantly higher than the rates of 53.3% and 33.0% in the nonembolization group, respectively. 18 Therefore, ICA embolization would further improve the survival rate of advanced rNPC in the Fudan rT staging. However, most medical institutions did not use the ICA embolization technique for patients with ICA invasion and even considered that rNPC with ICA invasion was contraindications to endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the article by Li and colleagues. 1 The authors described a novel technique for the management of large, recurrent nasopharyngeal cancers (NPC), and proposed surgical management of recurrent tumor stage 3 (rT3) and 4 (rT4) lesions adjacent to and invading the carotid artery. The study showed that employing long-segment carotid artery coil embolization from the parapharyngeal to the paraclival segments improved oncologic and perioperative outcomes.…”
Section: To the Editormentioning
confidence: 99%